A modular mobile robotic architecture for defects detection and repair in narrow tunnels of CFRP aeronautic components. (February 2019) - Negri, Simone Pio; Basile, Vito; Valori, Marcello; Gambino, Benedetto; Fassi, Irene; Molinari Tosatti, Lorenzo
Highlights: Manufacturing costs of a multi-spar box structure are relevant. Manufacturing defects in aeronautical CFRP components can cause its discard. Manual scarfing is currently carried out to repair external defects. A robotic solution is proposed to repair inaccessible defects inside narrow tunnels. A multi-functional modular architecture enables the execution of more repair stages. Abstract: Advanced composite structural components in aeronautics are characterized by very high production costs because of their dimensions, complex shapes and expensive forming equipment. For these components, such as horizontal stabilizers and wings, a defect occurrence is often critical because large part of inner surfaces, made of long and tapered narrow tunnels, are not reachable for repair operations. In these cases, the part is rejected with a relevant economic loss and high production costs. For this reason, aircraft constructors plan huge investments for defects avoidance during the forming processes of CFRP and to develop effective, robust and reliable repair tools and methods. Mobile robotics can play an important role, with specific systems capable of moving into narrow channels of wings structures (i.e. multi spar boxes) and repair it in accordance to technical standards. This paper describes an innovative mobile robot architecture for bonded repair scarfing operations on CFRP components. Targeting and responding to the demanding machining requirements, the functional-oriented design approach clearly highlights the advantages of a modular robotic solution. The mobile robotic architecture can be also applied in other fields with similar challenging manufacturing operations for further inspection, detection and machining operations. Graphicalabstact :